The Growing Role of Transportation Funding in Regional Habitat Conservation Planning. Issue 4 (1st October 2016) - Lederman, Jaimee; Wachs, Martin
Abstract : Problem, research strategy, and findings: Regional conservation initiatives struggle to meet funding needs when complying with the Endangered Species Act (ESA) of 1996 and need money early to pay for required planning and to acquire land to mitigate the impact of development. Transportation agencies struggle to comply with the ESA and have increasingly been willing to fund regional habitat conservation plans (RHCPs) to do so. We review documents from 22 RHCPs and interview representatives of 16 RHCPs to understand how transportation agencies have contributed to funding RHCPs. We find that transportation agencies mitigate their impacts and provide early and consistent financing to facilitate the planning process, help RHCPs establish initial conservation preserves, and allow RHCPs to capitalize on lower land prices during downturns in the development market. We only sample RHCPs in a few states, however, and these examples may not comply with laws in others. Many of the cases studied are recent; time is needed to assess their long-term success. We recommend further study to assess applications to sectors beyond transportation and beyond the areas we studied. Takeaway for practice: Transportation agencies have struggled to meet environmental requirements and habitat conservation agencies have typically considered transportation agencies threats to the environment. Where adversarial relationships can be overcome, partnerships between transportation and conservation programs can effectively finance habitat conservation while facilitating capital investments in transportation systems.